03.06 Understanding how epitope binding influences antibody dependent complement engagement for therapy of B-cell malignancies. (21st September 2022) - Bondza, S; Buijs, J; Lux, A
Abstract : Background: Monoclonal antibodies (mAbs) have the capacity to combine targeted therapy with immune activation through recruitment of immune cells and complement proteins via their Fc-terminus. For treatment of B-cell malignancies, mAbs targeting the B-cell surface marker CD20 are well established; with Rituximab, Ofatumumab and Obinutuzumab being most commonly used in the clinic. Even though these three mAbs are all of the IgG1 subclass they differ in their effector functions, especially in their ability to engage the complement system for B-cell depletion. Efforts have been made to relate the functional properties of these mAbs to molecular characteristics to allow for informed decisions when designing next generation therapeutics. Materials and Methods: Real-time interaction analysis was performed with LigandTracer to deduct the binding mechanism of CD20 antibodies and complement protein on live cell lines and primary B-cells. Efficiency of complement dependent cell killing was evaluated in vitro . Results: Ofatumumab displayed the most stable binding to CD20 driven by bivalent target engagement which was independent of antibody concentration. Rituximab could overall engage more in bivalent binding compared to Obinutuzumab, but for both antibodies, stabilization of the interaction due to bivalency decreased with increasing antibody concentration, resulting in dose-dependent apparent affinities. The interaction strength of the first complement component C1q to the Fc-terminus of cell-bound mAbs correlated positively with degree of bivalent binding for the mAbs to CD20. Kinetic analysis revealed two multivalent interaction components that represent C1q binding to low- and high-order IgG Fc-oligomers on the cell surface. The latter interaction component was characterized by more stable C1q capture and most dominant for Ofatumumab. Target cell killing through antibody dependent complement activation was more efficient with strong bivalent target engagement and high C1q binding stability. Conclusions: Taken together this implies that bivalent target engagement helps cluster CD20 on the cell surface leading to beneficial arrangement of IgG Fc for stable C1q capture through optimization of avidity effects, which translates to efficient activation of the complement cascade. These findings are strongly supported by recent structural data in the field and add to the understanding on how the binding mechanism influences immune activation for CD20 mAbs. Disclosure Information: S. Bondza: A. Employment (full or part-time); Significant; Ridgeview Instruments. J. Buijs: A. Employment (full or part-time); Significant; Ridgeview Instruments. A. Lux: None.